Ramadan intensity and subsequent student achievement - Erik Hornung; Guido Schwerdt; Maurizio Strazzeri (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
The observance of Ramadan has been widely associated with detrimental health effects as well as poor economic performance. Less attention has been given to the potential benefits generated by the social aspects associated with this religious practice. This column argues that Muslim students achieve higher scores in educational performance tests following a more intense Ramadan. This effect is explained by the formation of social capital and social identity among students sharing the intensive experience of this religious practice.
Keywords: 330